The Effectiveness of Acupuncture in Insomnia Patients: Meta Analysis - Putri, Kurnia Eka; Murti, Bhisma; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Insomnia is a disease that has a negative impact on the health and well-being of the sufferer. Insomnia can occur in anyone, both men and women with various ages of vulnerability and in individuals with various socioeconomic backgrounds. This study aims to examine the effectiveness of acupuncture in insomnia patients.Subjects and Method: Meta-analysis was performed with PICO which is presented as follows: the population in this study was insomnia patients aged 16-85. The intervention is in the form of acupuncture therapy. The comparison used was a sham/ placebo acupuncture. The outcome was insomnia. The meta-analysis study was applied to this study with electronic data sources: Clinical Key, Google Scholar, MEDLINE/ PubMed, Science Direct, Scopus. The article used is a full-text article with a randomized control trial (RCT) study design. There were 9 articles used in this study with a sample size of 649 people who were divided into two groups (372 people in the acupuncture group and 277 people in the sham / placebo acupuncture group). Articles were analyzed using the Review Manager 5.4 application. The results of this study aim to determine the Standardized Mean difference (SMD) and heterogeneity of the study sample.Results: There is high heterogeneity between one experiment and another (I2= 94%; p <0.001) so that what is used is the Random Effect Model (REM). The provision of acupuncture therapy was able to reduce the degree of insomnia with the Standardized Mean Different (SMD) of 0.98 compared to sham acupuncture (SMD= -0.98; 95% CI= -1.71 to -0.25; p = 0.008).Conclusion: The provision of acupuncture therapy was able to reduce the degree of insomnia with the Standardized Mean Different (SMD) of 0.98 compared to sham acupuncture.Keywords: Acupuncture, InsomniaCorrespondence: Kurnia Eka Putri. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Indonesia. Email: anggipag@gmail.com.Mobile: +628995212646.Indonesian Journal of Medicine (2021), 06(01): 42-51https://doi.org/10.26911/theijmed.2021.06.01.05.